The Relationship Between Law and Politics in the Government Regulation in Lieu of Law (Perppu) on Social Organizations - Aisy, Rohadhatul; Nte , Ngboawaji Daniel; Windiahsari, Windiahsari (Universitas Negeri Semarang, 2024)
Perppu Number 2 of 2017 on Amendments to Law Number 17 of 2013 on Social Organizations is an example of a legal product where there is a relationship between Law and Politics. With this Perppu, the government has disbanded one of the social organizations, namely Hizbut Tahrir Indonesia (HTI), which was deemed not in accordance with Pancasila and the 1945 Constitution and wanted to change the state's ideology. The Perppu on Social Organizations issued by the government was promulgated by the People's Representative Council (DPR) on November 22 2017, but there are several factions that still reject the law. After observed, it is known that the factions that agree to the promulgation of the Perppu are government parties and those that reject it are political parties. opposition. Apart from that, we know that social organizations are one of the wings of politics, which are very effectively used to boost the votes of political parties and mobilize the masses. This research aims to examine legal and political relations in Government Regulation in Lieu of Law (Perppu) Number 2 of 2017 on Amendments to Law Number 17 of 2013 on Social Organizations. The research results show that there are several substances in the Perppu that have given rise to controversy in society regarding criminal sanctions and the dissolution of social organizations. All legal products, including this Perppu, are not neutral; rather, they contain interests and biases, highlighting the close relationship between law and politics.